1624. Primary Care Physician Knowledge, Attitudes, and Diagnostic Testing Practices for Norovirus and Acute Gastroenteritis - Cardemil, Cristina (Open Forum Infect Dis, 2019)
BACKGROUND: Norovirus is a leading cause of acute gastroenteritis (AGE) across the age spectrum; candidate vaccines are in clinical trials. While norovirus diagnostic testing is increasingly available, stool testing may not be performed routinely, which can hamper surveillance and burden of disease estimates. Our objectives were to understand physicians’ stool testing practices in outpatients with AGE, and physician knowledge of norovirus, in order to improve surveillance and prepare for vaccine introduction. METHODS: Internet and mail survey on AGE and norovirus conducted January to March 2018 among national networks of primary care pediatricians (Peds), family practice (FP) and general internal medicine (GIM) physicians. RESULTS: The response rate was 59% (820/1,383). During peak AGE season, physicians estimated they ordered stool tests for a median of 15% (interquartile range: 5–33%) of their outpatients with AGE. Stool tests were more often available for ova and parasites, Clostridioides difficile, and bacterial culture (>95% for all specialties) than for norovirus (6–33% across specialties); even when available, norovirus-specific tests were infrequently ordered. Most providers were unaware that norovirus is a leading cause of AGE across all age groups (Peds 80%, FP 86%, GIM 89%) or that alcohol-based hand sanitizers are ineffective against norovirus (Peds 51%, FP 66%, GIM 62%). CONCLUSION: Physicians infrequently order stool tests for outpatients with AGE, and have knowledge gaps on norovirus prevalence and hand hygiene for prevention. Understanding the limitations of surveillance that relies on physician-ordered stool diagnostics, and closing physician knowledge gaps, can help support norovirus vaccine introduction. DISCLOSURES: All authors: No reported disclosures.